PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DENGAN STRATEGI TEAM QUIZ TERHADAP PRESTASI BELAJAR SEJARAH SISWA KELAS XI IPS SMA NEGERI 8 BANDA ACEH - Tomi Hidayat; Anwar Yoesoef; Nurasiah . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
The research entitled "The Influence of Cooperative Learning Model of Group Investigation Type with Team Quiz Strategy on Student Achievement of History Grade XI IPS of SMA Negeri 8 Banda Aceh" is aimed to analyze the influence of cooperative learning model of Group Investigation type with Team Quiz strategy on IPS student achievement in grade VIII SMA Negeri 8 Banda Aceh. The approach that use in this research are a quantitative and the type of the is experimental research. The population in this research is all students of class XISMA Negeri 8 Banda Aceh which amounts to 83 students and consists of 3 classes. The sample is the students of class XI IPS.2 as the experimental class and the students of class XI IPS.1 as the control class consisting of 24 students each. The technique of collecting the data are tests and documentation. The technique of analysisthe data in this research is (1) calculate the mean value; (2) calculate the variance and standard deviation; (3) normality test; (4) homogeneity test of variance; and (5) t-test. Based on the technique of data analysis, the average value of the experimental class is 80,3 and the control class is 71,6. The variance and standard deviation of the experimental class were 79,24 and 8,90 while the control classes were 47,64 and 6.90. The experimental class normality test is 2,54 and the control class is 1,05. The homogeneity test of experimental class variance and control class was 1.66. And the t-test result is 3.90. Based on the data analysis above, it can be concluded that the average value of eskperimen class is higher than control class. The data distribution of the final test score of the students in the experimental class and the control class is normally distributed based on the significant level of x2countx2tablethat is2,547.81 and 1,057.81. To test the homogeneity of variance is Fcount≤ Ftable is 1.66 ≤ 2.09, then the variance of experimental class data and control class is homogeneous. Results of data processing using t-test analysis obtained tcount = 3.90 while ttable = 2.02. Means that tcountttable is 3.90 2.02, thus according to the testing criteria then H0 is rejected and Haisaccepted. Keyword:  cooperative learning,group investigation, team quiz,learning achievement.